Developing and trialing a measure of group thinking. (April 2017) - Wegerif, Rupert; Fujita, Taro; Doney, Jonathan; Perez Linares, Julieta; Richards, Andrew; van Rhyn, Claire
Abstract: This paper offers a critical review of the issue of assessing the quality of group thinking, describes the development of a Group Thinking Measure that fills a gap revealed by the literature and illustrates the use of this measure, in combination with interpretative discourse analysis, as a way of distinguishing those behaviors that add value to group thinking from those behaviors that detract value. The Group Thinking Measure combines two tests of equal difficulty, one for individual use and one for use by triads. This enables a measure not only of how well groups are thinking together but also a correlation between individual thinking and group thinking. This innovation gives an indication of whether or not working in a group adds value and so the extent to which a classroom culture supports collaborative thinking. Highlights: Current research on measuring group thinking has limitations. We report on the developing a Group Thinking Measure. This offers a way to assess the teaching of effective dialogue. Case studies illustrate how this tool can support research on group thinking.